Change in self-reported outcomes and objective physical function over 7 years in middle-aged subjects with or at high risk of knee osteoarthritis. Issue 4 (17th August 2007) - Roos, E M; Bremander, A B; Englund, M; Lohmander, L S
Abstract : Objective: In the present work, we describe the clinical course and predictors of change in self-reported outcomes and objectively assessed physical function over time in middle-aged subjects at high risk of, or with knee osteoarthritis (OA). Methods: We examined 259 subjects (mean (SD) age 52.6 (10.4)) at mean 18 and 25 years after previous meniscectomy and 50 population-based age- and sex-matched reference subjects with the Knee injury and Osteoarthritis Outcome Score (KOOS), one-leg hop for distance and number of knee-bendings in 30 s. Radiographic OA was defined as equivalent to Kellgren and Lawrence grade 2 or worse. Results: At first assessment, meniscectomised subjects reported worse pain, function and quality of life compared with the reference group (p<0.001). They also performed fewer knee-bendings per 30 s (27 vs 31, p = 0.02). The meniscectomised patients worsened over the 4–10-year observation time in all measured outcomes (p<0.001), and to a greater extent than the reference group in pain (−5, 95% CI −10 to 0) and one-leg hop (−11, 95% CI −18 to −3). Being a woman, or having radiographic knee OA, enhanced the worsening in self-reported and objectively assessed outcomes. Older age and a higher body mass index (BMI) influenced objectively assessed physical function, but not self-reported outcomes. Conclusion: Worsening over time in knee-related pain and function is greater in meniscectomised subjects compared with reference subjects. Rehabilitative efforts may be warranted in middle-aged meniscectomised patients, especially in women and those who have developed radiographic knee OA, who are at greater risk of worsening.